The shapes of fragments from catastrophic disruption events: Effects of target shape and impact speed. (March 2015) - Durda, Daniel D.; Campo Bagatin, Adriano; Alemañ, Rafael A.; Flynn, George J.; Strait, Melissa M.; Clayton, Angela N.; Patmore, Emma B.
Abstract: We conducted impact experiments at the NASA Ames Vertical Gun Range in the context of an ongoing set of experiments to investigate both target shape and impact speed effects on fragment shapes and mass–frequency distributions in collisions on basalt targets. In this work we present the first part of that set, regarding mostly target shape effects. We impacted both irregularly-shaped and spherical basalt targets at speeds ranging from ~4–6 km/s. We obtained mass–frequency distributions from fragments recovered from the impact chamber and measured fragments shapes using a combination of image analysis and manual measurements with a caliper. We find that the characteristics of the mass–frequency distributions and the range of fragment shapes show no significant dependence on target shape (i.e., flat, 'shell-like' fragments are produced in impacts into irregularly-shaped targets as well as spherical ones). We note that many thin, plate-like impact fragments seem to originate from lower-speed impacts and can originate from the interior of the targets (in addition to the flattened fragments often seen to origin from the near-surface spall zone in cratering impacts). We measure the porosity of aggregates made by artificially (but randomly) reassembling fragments from each impact to be on the order of 50%, significantly larger than that for hexagonal lattice and random packing of equal sized spheres. Highlights: Impact experiments to investigate effect of target shape on fragment shapes. Fragment shapes show no significant dependence on target shape. Thin, plate-like impact fragments originate from lower-speed impacts. Porosity of aggregates of reassembled fragments is of order of 50%.